Pemanfaatan Jurnal Elektronik Oleh Mahasiswa Di Perpustakaan Pusat Universitas Warmadewa - Lestari, Ni Made Nita; Haryanti, Ni Putu Premierita; Kastawa, Made (Jurnal Ilmiah D3 Perpustakaan, 2019)
ABSTRACT This study aims to explain and analyze the influence of Electronic Journal users perception on attitudes and the use of Electronic Journal. This research is located in the Central Library of Warmadewa University. The data collection technique used in the form of a questionnaire using 2 independent variables: Percevied Easy of Use and Percevied Usefulness, also using two dependent variables: Attitude Towad Using and Actual Usage. The analysis technique used is multiple linear regression analysis and test the results of the study using an application called SPSS Version 25. The results of the study were tested by hypothesis testing with sig. t count ? alpha (? = 0.05), it can be concluded that electronic journals have been useful for students using library at the Warmadewa University Central Library. Keywords: Utilization, Journal, Electronic